Cultivating Imagination in Adult Education - Ron Norman (Adult Education Research Conference, 2000)
The purpose of this paper is to examine the role of imagination in teaching and learning, and to explore how Kieran Egan’s (1992) concept of "imaginative learning" contributes to adult education theory and practice.